Sheet Metal 2021 - Merklein, Marion; Duflou, Joost; Fratini, Livan; Hagenah, Hinnerk; Martins, Paulo A.F.; Meschut, Gerson; Micari, Fabrizio (Trans Tech Publications, 2021)
This volume holds selected papers of the 19th International Conference on Sheet Metal 2021, which provided an excellent platform for the exchange of knowledge for scientists and industry representatives from all over the world. The conference addressed current research and future trends concerning topics related to sheet metals. Besides innovative mechanical joining technologies and the latest developments concerning bonding and welding, the wide-ranging field of sheet metal forming was one of the major issues of the conference. Moreover, SheMet 2021 dealt with research activities regarding incremental forming. As manufacturing technologies are closely associated with the materials to be processed, characterization also represented a key topi
Keywords: Alloy; Bending; Bonding; Forming; Friction; Hardness; Incremental Forming; Joining; Mechanical Properties; Rolling; Sheet Metal; Simulation; Steel; Stress; Surface; Welding